Hume's moral theory - Mackie, J. L. (John Leslie) (International library of philosophy., 1980)
Hume's moral theory was the most important contribution to the sustained debate among the British Moralists of the 17th and 18th centuries. J.L. Mackie's classic text examines this debate and provides an excellent introduction to some of the main problems of moral philosophy.